Improvement of Brain SPECT by Stabilization of Tc-99m-HMPAO with Methylene Blue or Cobalt Chloride - Barthel, H.; Kämpfer, I.; Seese, A.; Dannenberg, C.; Kluge, R.; Burchert, W.; Knapp, W. H. (Nuklearmedizin - NuclearMedicine, 1999)
Aim: This present study was carried out to investigate whether stabilization of Tc-99m-HMPAO with methylene blue (MB) or cobalt chloride (CC) causes a sensible improvement in image quality and how cerebral to noncerebral activity ratios compare with those of Tc-99m-ECD. Methods: 30 minutes after preparation 400-600 MBq unstabilized Tc-99m-HMPAO (N = 35 patients), Tc-99m-HMPAO added with MB (N = 24 patients), added with CC (N = 30 patients) or Tc-99m-ECD (N = 28 patients) were injected. Radiochemical stability was measured in vitro with three chromatographical methods. Image quality was assessed quantitatively using two ratios, one of them determined by count densities of brain/scalp (QS), the other one by count densities of brain/ nose (QN). In addition, image quality (0 = bad, 3 = excellent) and background activity (0 = high, 3 = no) were visually assessed by three independent observers. Results: In contrast to unstabilized Tc-99m-HMPAO the integrity of the complexes of MB-Tc-99m-HMPAO, CC-Tc-99m-HMPAO and Tc-99m-ECD decreased only by a few percent during a period of 2 hours after reconstitution (66.8 ± 9.9 vs. 93.0 ± 2.5, 91.8 ± 1.9 and 96.9 ± 1.4%, p <0.001). Qs and Qn (m.v. ± SD) differed significantly between studies using unstabilized Tc-99m-HMPAO (3.0 ± 0.4 and 2.1 ± 0.3), MB-Tc-99m-HMPAO (3.4 ± 0.4 and 2.3 ± 0.3), CC-Tc-99m-H M PAO (3.6 ± 0.6 and 2.6 ± 0.4) and those using Tc-99m-ECD (4.3 ± 0.7 and 4.8 ± 1.4; p <0.05 and <0.001). Stabilization with CC or MB resulted in significant higher scoring of image quality and lower scoring of background activity in comparison to that of unstabilized Tc-99m-HMPAO, without reaching the scores obtained with Tc-99m-ECD. Conclusions: It is concluded that stabilization of Tc-99m-HMPAO with MB or CC definitely improves image quality in rCBF-SPECT, without reaching that of Tc-99m-ECD. Improvement of image quality results from the reduction of the amount of decomposition products that contribute to considerable extracerebral activity.
Keywords: Tc-99m-HMPAO; methylene blue; cobalt chloride; Tc-99m-ECD; in vitro stabilit